2019
DOI: 10.1111/iju.14122
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil is sufficiently effective for severe chronic prostatitis/chronic pelvic pain syndrome in patients with benign prostatic hyperplasia

Abstract: Objectives: To investigate the efficacy of tadalafil for patients with benign prostatic hyperplasia and especially with chronic prostatitis/chronic pelvic pain syndrome.Methods: Tadalafil 5 mg was given each morning for 12 weeks to patients diagnosed as having either moderate or severe lower urinary tract symptoms. Voiding symptoms were compared between patients with a high (>4; high group) and low (<4; low group) pain subscore of the National Institutes of Health Chronic Prostatitis Symptom Index before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Although several PDE5Is (sildenafil, tadalafil, and vardenafil) have been reported to exert efficacy on LUTS-BPH patients, only tadalafil has been approved by the FDA to treat patients with BPH (Hiramatsu et al, 2020). PDE5Is were initially developed to treat ED.…”
Section: The Efficacy Of Pde5is In Bph Patientsmentioning
confidence: 99%
“…Although several PDE5Is (sildenafil, tadalafil, and vardenafil) have been reported to exert efficacy on LUTS-BPH patients, only tadalafil has been approved by the FDA to treat patients with BPH (Hiramatsu et al, 2020). PDE5Is were initially developed to treat ED.…”
Section: The Efficacy Of Pde5is In Bph Patientsmentioning
confidence: 99%
“…The coexistence of these conditions is interesting in that evidence suggests a link between prostatitis and ED though the reason is unclear. One study had shown that tadalafil, a classic drug for ED, is also effective for treating prostatitis [ 10 ]. In recent years, lots of articles have revealed that a high prevalence of ED ranges from 15.0% to 40.5% among patients with CP/CPPS in China; it is not enough to explain the relationship based on the current research data [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IPSS scores were very significantly decreased after both treatments and the results have persisted up to the 12‐month follow‐up. Hiramatsu et al 31 have recently found that tadalafil administration led to a larger decrease of IPSS scores in patients with benign prostatic hyperplasia that also had more severe pain scores, compared to those that did not experience high levels of pain. That is consistent with our results, as all of the patients in our study had high pain scores and have shown very pronounced IPSS improvement after both treatments (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary symptoms were evaluated using different outcome measures: Objectively, by measuring the maximum urethral flow value (Q-max) using uroflowmetry; and subjectively, using the International Prostate Symptom Score (IPSS) questionnaire, which consists of seven questions concerning urinary symptoms and one question concerning quality of life. 15 The IPSS total score range is from 0 to 35, from asymptomatic (score 0), mildly symptomatic (1-7), moderately symptomatic (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) to severely symptomatic (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%